Association between sick sinus syndrome and atrial fibrillation: A systematic review and meta-analysis. (15th June 2023) - Liu, Ying; Zheng, Yi; Tse, Gary; Bazoukis, George; Letsas, Konstantinos; Goudis, Christos; Korantzopoulos, Panagiotis; Li, Guangping; Liu, Tong
Abstract: Aims: Sick sinus syndrome (SSS) and atrial fibrillation (AF) frequently coexist and show a bidirectional relationship. This systematic review and meta-analysis aimed to decipher the precise relationship between SSS and AF, further exploring and comparing different therapy strategies on the occurrence or progression of AF in patients with SSS. Methods and results: A systematic literature search was conducted until November 2022. A total of 35 articles with 37, 550 patients were included. Patients with SSS were associated with new-onset AF compared to those without SSS. Catheter ablation was associated with a lower risk of AF recurrence, AF progression, all-cause mortality, stroke and hospitalization of heart failure compared to pacemaker therapy. Regarding the different pacing strategies for SSS, VVI/VVIR has higher risk of new-onset AF than DDD/DDDR. No significant difference was found between AAI/AAIR and DDD/DDDR, as well as between DDD/DDDR and minimal ventricular pacing (MVP) for AF recurrence. AAI/AAIR was associated with higher risk of all-cause mortality when compared to DDD/DDDR, but lower risk of cardiac death when compared to DDD/DDDR. Right atrial septum pacing was associated with a similar risk of new-onset AF or AF recurrence compared to right atrial appendage pacing. Conclusion: SSS is associated with a higher risk of AF. For patients with both SSS and AF, catheter ablation should be considered. This meta-analysis re-emphasizes that high percentage of ventricular pacing should be avoided in patients with SSS in order to decrease AF burden and mortality. Highlights: In this meta-analysis, we systematically analyzed the impact of sick sinus syndrome on new-onset atrial fibrillation, atrial fibrillation recurrence and atrial fibrillation progression. We deeply discussed the relationship between sick sinus syndrome and atrial fibrillation from various perspectives, including the surgical strategy for tachycardia-bradycardia syndrome, the choice of pacemaker treatment modality for patients with sick sinus syndrome, and the effect of right atrial electrode position on the occurrence and prognosis of atrial fibrillation. This systematic review and meta-analysis provides evidence for the prevention of atrial fibrillation and the choice of pacemaker treatment options for patients with sick sinus syndrome, which is of significant clinical implications.